WTO disciplines on agricultural support: Philippine WTO domestic support notification: WTO domestic support update - Cororaton, Caesar B. (2013)
This is a WTO domestic support notification update prepared for the International Food Policy Research Institute (IFPRI) on the chapter for the Philippines in WTO Disciplines on Agricultural Support: Seeking a Fair Basis for Trade (Orden, David, David Blandford, and Tim Josling, editors), 2011, Cambridge: Cambridge University Press